2021
DOI: 10.3390/brainsci11121579
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and the Right Hemisphere: Editorial

Abstract: The hypothesis assuming that the right hemisphere may play a critical role in emotional processing was raised by clinical data which showed that patients with right brain lesions often show abnormal patterns of emotional behavior [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…It is noteworthy that in both conditions the classical parieto-premotor territories of the mirror neuron network are activated, especially in the right hemisphere in the emotional condition and in the left hemisphere in the non-emotional one. The stronger right hemisphere activation is in line with the aforementioned evidence that this hemisphere is crucial to process emotions ( Gainotti 2021 ). In contrast, the stronger activation observed in the left hemisphere during the non-emotional condition seems to be related to the presence of verbal material.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is noteworthy that in both conditions the classical parieto-premotor territories of the mirror neuron network are activated, especially in the right hemisphere in the emotional condition and in the left hemisphere in the non-emotional one. The stronger right hemisphere activation is in line with the aforementioned evidence that this hemisphere is crucial to process emotions ( Gainotti 2021 ). In contrast, the stronger activation observed in the left hemisphere during the non-emotional condition seems to be related to the presence of verbal material.…”
Section: Discussionsupporting
confidence: 87%
“…These results indicate that, besides processing the emotional content, these subcortical sectors are also modulated by the form in which the emotion is expressed (high vs. low). It is important to note that, as already demonstrated by many neurological and functional studies regarding the emotional processing, the perception of emotional laughing mainly involved the right hemisphere ( Gainotti 2021 ).…”
Section: Discussionmentioning
confidence: 77%
“…It is widely known that the brain has partial lateralization, with the left hemisphere primarily responsible for word processing and the right hemisphere playing a critical role in emotion processing [ 44 ]. Some scholars have suggested that emotional words can induce corresponding emotions, and unattended emotional words tend to receive priority in attentional resource competition, leading to attention bias [ 45 ]. As a result, negative stimuli can elicit stronger emotional effects in the right hemisphere [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that both emotions (Gainotti, 2021) and music (Wang & Agius, 2018) are processed predominantly by the right hemisphere (RH), and that these functions are inextricably linked (Trimble & Hesdorffer, 2017). In a study by Blood et al (1999), participants listened to pleasant and unpleasant (dissonant) music while changes in cerebral blood flow were measured using positron emission tomography (PET).…”
Section: Music and Emotion Lateralizationmentioning
confidence: 99%